(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
What should be the water pressure at the site with an artesian well refers to the intensity of water pressure. A very important parameter that affects not only the comfort of living in the house, but also the technical condition of the pumping device, as well as sanitary appliances. Regular monitoring with the use of pressure gauges will help to make sure that the values are normal and, if necessary, adjust them. Recommended values are specified in GOST and other technological standards. This article summarizes the main solutions to the problems of emergency situation due to differential pressure in private homes.